The challenge of fundamentalism : political Islam and the new world disorder - Tibi, Bassam (Berkeley, Calif. : University of California Press, 2002)
A text which suggests that Islamic fundamentalism is a result of Islam's confrontation with modernity. The author provides an analysis of the politicization of religion and, as an alternative to fundamentalism, he proposes a compact based on secular democr.
Acy and human rights.
The context: globalization, fragmentation, and disorder -- The study of Islamic fundamentalism and the scope of the inquiry -- World Order and the legacy of Saddam Hussein -- The sociocultural background and the exposure to cultural modernity -- Cultural fragmentation, the decline in consensus, and the diffusion of power in world politics -- The crisis of the Nation-State: Islamic, Pan-Arab, ethnic, and sectarian identities in conflict -- The fundamentalist ideology: context and the textual sources -- The idea of an Islamic State and the call for the implementation of the Sahri'a/Divine Law -- Democracy and democratization in Islam: an alternative to fundmentalism -- Human rights in Islam and the West: cross-cultural foundations of shared values.
Originally published: 1998.
Includes bibliographical references (pages 215-251) and indexes.
JSTOR
Keywords: Islam and politics; Islamic fundamentalism; Islam -- 20th century; Islam -- 21st century; Islam -- 1800-; Intégrisme islamique; Islam -- Histoire -- 20e siècle.; Islam -- Histoire -- 21e siècle.; 11.84 Islam: other; 89.29 political ideologies: other; RELIGION / Islam / General; Islam; Islam and politics; Islamic fundamentalism; Islam; Fundamentalisme; Intégrisme islamique; Islam; Modernité.; Ordre mondial; Politique mondiale; Since 1800